microRNA-9-5p protects liver sinusoidal endothelial cell against oxygen glucose deprivation/reperfusion injury - Duan Yi (De Gruyter, 2021)
Maintenance of the function and survival of liver sinusoidal endothelial cells (LSECs) play a crucial role in hepatic ischemia/reperfusion (I/R) injury, a major cause of liver impairment during the surgical treatment. Emerging evidence indicates a critical role of microRNAs in I/R injury. This study aims to investigate whether miR-9-5p exerts a protective effect on LSECs.